Vault run-up characteristics and their influence on high level female gymnastics performance - Massaro, A.; Emerenziani, G. P.; Broccatelli, M.; Baldari, C.; Guidetti, L. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Vault is one of the four apparatus of the female gymnastics. Despite a large studies about the biomechanical aspect of the Vault skills, there are currently a paucity of data regarding the effectiveness of Vault run-up on exercise successful evaluated by judge score (Sands and McNeal, 1995¸ Krug et al., 1998). The aim of this study was to analyze the effects of vault run up parameters on quality vaulting performance. Methods Sixteen female gymnasts (age: 18±3 yrs; height: 154.1±7.3 cm; weight: 44.5±6.1 kg) of four different national teams (Italy, Brazil, Romania and Belarus) performed vault exercise during international competition (Mediterraneo Gym Cup). All the gymnasts performed vaults of Yourchenko type, which is characterized by a round off before the springboard impact. During vault performance contact time (CT), flight time (FT), step length (SL), step height (SH), run-up velocity (RV) and acceleration (RA) were assessed step by step using Optojump system (Microgate, Bolzano, Italy) along runway mat. Moreover judges` score were recorded. Judges` score is made up of A and B score. A score corresponds to the skill difficult, and B score corresponds to the judges` deductions. The final score results from the difference between A and B score. Results Correlation analysis was used to assess the relationship between all the run-up variables and judges` score. Last run-up step CT (0.12±0.01 s) and hurdle CT (0.11±0.01 s) were significantly (p<0.05) related to B (9.0±2.7 points; r= -0.515 and r= -0.512, respectively) and final scores (14.4±7.0 points; r= -0.5 and r= -0.512, respectively). No significant correlations were found between all the other variables and judges` score. Discussion Our results, according with literature, showed that run-up velocity did not appear correlated with vaulting performance (Sands and Cheetham, 1986). This could be due to the gymnastics` focus on the springboard approach during the run-up, since before the springboard impact they have to be focused also on the round off. Our main finding was that higher judges` final scores were related to shorter contact time of the final run-up step and of the hurdle. These results showed how the vault run-up is characterized also by technical variables and not only by kinematics variables. Therefore future research must focus on last run-up step and on hurdle characteristics rather than on run-up speed. References Krug J, Knoll K, Kothe T, Zocher HD. (1998). ISBS`98 XVI International symposium on biomechanics in sports, Vol I p. 160-163. Sands WA, Cheetham PJ. (1986). Tecnique, 6, 10-14. Sands WA, McNeal JR. (1995). Tecnique, 15(5), 8-10.